On the Italian species of Drusilla Leach, 1819, with a note on D. taygetana Assing (Coleoptera: Staphylinidae, Aleocharinae). - Assing, Volker (Contributions to Entomology = Beiträge zur Entomologie, 2006)
The Italian representatives of the aleocharine genus Drusilla Leach, 1819 are revised. Three species are recognised; the presence of a fourth species, D. erichsoni (Peyron, 1857), in Italy is doubtful. The enormous variation of external characters and the spermatheca of D. italica (Bernhauer, 1903) is described, illustrated, and discussed. It is interpreted as clinal rather than interspecific or intersubspecific variation. Based on examined records, the distributions are mapped. A key to species is provided. The previously unknown male sexual characters of D. taygetana Assing, 2005 are described and illustrated.KeywordsColeoptera, Staphylinidae, Aleocharinae, Drusilla, Italy, Greece, taxonomy, new records, key to species, distribution.Nomenclatural Actsitalica (Bernhauer, 1903) (Drusilla), Lectotype described as Astilbus italicus